Beyond carrots and sticks. Exploring faculty motivation to join a digital health professions educator program - Schumann, Marwa; Lehmann, Martin; Peters, Harm (Frontiers in Medicine, 2025)
IntroductionFaculty development programs in the health professions are essential in addressing the evolving and expanding roles of educators. These programs have become a cornerstone of organizational development and contribute significantly to improving student learning. However, the motivation of faculty to engage in such programs is often challenged by the significant demands of their clinical responsibilities and already busy schedules. This study aims to explore the motivation of teaching health professionals to voluntarily participate in the Digital Health Professions Education (d-HPE) program, a 200-h certification program at the Charité - Universitätsmedizin Berlin to train digital teaching skills and competencies.MethodsIn this qualitative study, we analyzed the motivation letters from faculty members who volunteered to participate in the d-HPE program. We used coding based on Self-Determination Theory (SDT) as a framework for analysis with three main themes: autonomy, competence and relatedness. Within autonomy, the sub-themes were intrinsic motivation and self-directed choices. Competence included the sub-themes of mastery of teaching practices and digital skill development. Relatedness included the sub-themes of interprofessional collaboration and mentorship.ResultsA total of 21 motivational letters were analyzed from two d-HPE cohorts, representing diverse health professional backgrounds and career stages. Analysis of the autonomy theme revealed an intrinsic motivation shaped by early teaching experiences and a self-directed decision to pursue advanced qualifications. The competence theme reflected the need to master evidence-based teaching practices and to develop advanced digital skills, with the COVID-19 pandemic as a driving factor. The relatedness theme demonstrated the importance of inter-professional collaboration and mentorship in promoting educational innovation across disciplines and institutions.DiscussionThe motivation of health professions educators to participate in faculty development programs goes beyond the traditional 'carrots and sticks' of external rewards or punishments constellation; it is rooted in their intrinsic motivation to improve teaching qualifications and fulfill their role in digital education. Despite the demands of a busy clinical and professional work schedule, active engagement in intensive faculty development programs is aligned with the need for interprofessional networking and the evolving demands of digital education.